Oesophageal atresia in newborns: diagnosis, treatment, and perioperative management: a systematic review - Szyda, Kamila; Lipowska, Klaudia; Mazurek, Weronika; Malczyk, Agnieszka; Cichowska, Zuzanna; Wawrzeczko, Natalia; Paluszyńska, Dorota; Królak-Olejnik, Barbara (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Oesophageal atresia (OA) is one of the most common and severe congenital defects of the oesophagus, often accompanied by the occurrence of the tracheoesophageal fistula (TEF). The process of determining the risk factors and the direct causes that contribute to its development is not yet completely understood. It is considered that multiple genes play a significant role in promoting this phenomenon, with most cases leading to TEF formation. The authors specify the importance of prenatal and postnatal diagnosis to determine the presence of OA and promptly stabilise haemodynamically newborns, enabling surgery to be performed as soon as possible. The thoracoscopic method has been recognized as a routine procedure for the treatment of OA. Additionally, both preoperative and postoperative management are extremely crucial to prevent any further complications in newborns.